ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KESETIAAN KONSUMEN MEREK MINUMAN GULU-GULU DI KOTA DENPASAR PROVINSI BALI - Nyoman Wahyu Widiana (Universitas Mahendradatta, 2022)
This study aims to determine consumer attitudes and satisfaction with consumenloyalty gulu-gulu brand drinks, where the population used in this activity is the people ofDenpasar city who have ever drank brand gulu-gulu drinks whose number is unknown(unknown population) with a sample of 96 people. Data collection techniques which is usedis literature study, observation and questionnaire with one sample test analyse .The results oftesting the validity of each research instrument statement on the variables of consumerattitudes and consumer satisfaction are valid because they are above the validity standard,which is > 0.300. Based on the SPSS output of the reliability test of the variables ofconsumer attitudes and consumer satisfaction in the statement. reliability because it is morethan 0.6 . test one sample formula t-test one sample. The value of t table can be calculatedusing dk=n-1 (96-1=95) with a degree of error of 5%, (0.05) then the value of t table = 1.665, because the value of tcount is greater than ttable (65.219> 1.665) then it falls in the area ofacceptance Ha means that Ha accepts and Ho is rejected, so consumer attitudes and customersatisfaction are above the predetermined criteria, namely 70%. Suggestions for companies arethat companies must be able to innovate both in terms of taste, packaging and otheradvantages so that consumers can increase customer satisfaction which will have an impacton consumer attitudes towards products.